Access to primary healthcare services among adults with disabilities in Brazil - Veronika Reichenberger; Maria Eduarda Lima de Carvalho; Tom Shakespeare; Shaffa Hameed; Tereza Maciel Lyra; Maria do Socorro Velo de Albuquerque; Loveday Penn-Kekana; Christina May Moran de Brito; Luciana Sepúlveda Köptcke; Hannah Kuper (Revista de Saúde Pública)
ABSTRACT OBJECTIVE To investigate perspectives of people with disabilities in Brazil regarding the access to primary healthcare. METHODS In-depth interviews were conducted with 44 individuals with disabilities in Pernambuco, Distrito Federal, and São Paulo between March 2020 and November 2021. These interviews were transcribed, coded, and analysed thematically, using the Levesque framework to identify healthcare access barriers. RESULTS Participants expressed a solid understanding of their healthcare needs and existing obstacles. However, individuals with hearing and visual impairments experience challenges because of communication barriers. In Pernambuco, the Community Health Agent was often the initial point of contact for primary care services. Public transportation lacked accessibility, from buses to driver attitudes, posing difficulties for people with disabilities. More accessible transportation and improved urban infrastructure could enhance service access. High medication costs were reported due to limited healthcare unit availability. Communication accessibility issues, inadequate audio-visual resources and equipment were also identified as barriers. Attitudinal barriers among healthcare professionals and subpar home visit services further hinder access. CONCLUSION To address these challenges and improve the well-being of individuals with disabilities in Brazil, comprehensive action is essential. This includes leadership, governance, and resource allocation reforms to meet healthcare needs. Initiatives like disability-focused training for service providers, enhanced transportation options, improved information accessibility, and increased support from community healthcare workers can collectively enhance the lives of people with disabilities.